Differences in Sociodemographic Characteristics and Treatment Refusal Between Lone and Multiple Perpetrator Rapists - Giménez-Salinas Framis, Andrea (International journal of offender therapy and comparative criminology, 2026)
Studies that compare lone and multiple perpetrator rape offenders often use police files. This study explores the differences between lone and multiple perpetrator rapists using a sample of 172 convicted sexual offenders. The first objective is to explore sociodemographic differences between the two groups of perpetrators. Differences are found in offenders? age, the use of drugs or alcohol, the release phase, sexual behavior, the use of a vehicle, the place and time of the assault, and victim characteristics. The second objective is to explore differences between the two groups regarding the number of perpetrators. No differences are found, except for the presence of a leader in groups of three or more perpetrators. Finally, no differences are found regarding treatment variables (responsibility assumption, treatment program participation, program dropout or expulsion, and reconviction rates) that support a different profile for the purpose of intervention.